2017
DOI: 10.1038/nclimate3262
|View full text |Cite
|
Sign up to set email alerts
|

An observation-based constraint on permafrost loss as a function of global warming

Abstract: Permafrost, which covers 15 million km 2 of the land surface, is one of the components of the Earth system that is most sensitive to warming 1,2 . Loss of permafrost would radically change high-latitude hydrology and biogeochemical cycling, and could therefore provide very significant feedbacks on climate change [3][4][5][6][7][8] . The latest climate models all predict warming of high-latitude soils and thus thawing of permafrost under future climate change, but with widely varying magnitudes of permafrost th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
255
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 337 publications
(264 citation statements)
references
References 27 publications
(25 reference statements)
6
255
0
3
Order By: Relevance
“…Ground thermal regime is strongly coupled with average atmospheric conditions and is often characterized by using average annual air temperature or cumulative temperature sums (e.g., freeze and thaw days; Chadburn et al, 2017;Gruber, 2012;Smith, 1975). In addition, precipitation conditions affect ground surface temperatures through water infiltration to soil column causing advective heat transfer and modifying thermal properties of the soil (heat capacity and thermal conductivity; Weismüller et al, 2011;Westermann et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Ground thermal regime is strongly coupled with average atmospheric conditions and is often characterized by using average annual air temperature or cumulative temperature sums (e.g., freeze and thaw days; Chadburn et al, 2017;Gruber, 2012;Smith, 1975). In addition, precipitation conditions affect ground surface temperatures through water infiltration to soil column causing advective heat transfer and modifying thermal properties of the soil (heat capacity and thermal conductivity; Weismüller et al, 2011;Westermann et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high importance of the Arctic Ocean and permafrost-dominated sub-arctic continental zones in the global carbon cycle and the high vulnerability of circumpolar zones to climate warming [20][21][22], numerous studies have been devoted to the biogeochemistry of organic carbon and nutrients in large rivers of the circumpolar zone [3,[23][24][25][26][27][28][29][30]. The main source of information on long-term fluxes of dissolved and suspended material from Northern Eurasia to the Arctic Ocean is data from the Russian Hydrometeorological Survey (RHS) collected at key gauging stations of almost all major Russian Arctic rivers [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Chadburn et al (2017) suggested that permafrost is more sensitive to global warming than previously believed: their study estimated that climate stabilization at 2°C greater than pre-industrial levels would eventually translate into a permafrost reduction of more than 40 per cent. However, it is the thawing of the permafrost (another tipping point of the Earth's climate system) that underlies large areas of the boreal that might have the most severe impact on the forests' resilience by changing the continental hydrological system, this phenomenon could permanently alter the local weather patterns to which boreal forests have adapted, potentially triggering the release of enormous amounts of GHGs.…”
Section: Boreal Forestsmentioning
confidence: 99%